2016
DOI: 10.5902/1980509825031
|View full text |Cite
|
Sign up to set email alerts
|

GERMINAÇÃO E REINDUÇÃO DA TOLERÂNCIA À DESSECAÇÃO EM SEMENTES DE <i>Senna multijuga</i> (RICH.) IRWIN ET BARN

Abstract: RESUMOO objetivo deste trabalho foi analisar diferentes métodos de superação de dormência, condições ótimas de germinação, tais como luz, temperatura, e possível reindução da tolerância à dessecação em sementes de Senna multijuga. Foram testados dois métodos de superação de dormência: imersão em água com temperatura inicial de 100ºC (água quente) e imersão em água com temperatura constante a 100ºC por 20 segundos (água fervente), ambos os tratamentos seguidos de repouso fora do aquecimento por 24 horas. Para o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…There are alternative methods for ex situ storage of recalcitrant seeds, but specific studies for R. grandis are required for further conclusions. These methods must consider the reduction of metabolism, or induction of desiccation tolerance in sensitive seeds, with the use of PEG (Polyethyleneglycol) and ABA (exogenous abscisic acid) in osmotic solutions, partial dehydration (drying the seed to its lowest possible water amount), which may increase longevity, and also the excision of the embryonic axis followed by cryopreservation (Bonjovani 2011;Ribeiro et al 2016a). Silva-Júnior & Pereira (2009) and Lorenzi (2009) also describe R. grandis germination with rates around 50% when sown soon after harvest.…”
Section: Discussionmentioning
confidence: 99%
“…There are alternative methods for ex situ storage of recalcitrant seeds, but specific studies for R. grandis are required for further conclusions. These methods must consider the reduction of metabolism, or induction of desiccation tolerance in sensitive seeds, with the use of PEG (Polyethyleneglycol) and ABA (exogenous abscisic acid) in osmotic solutions, partial dehydration (drying the seed to its lowest possible water amount), which may increase longevity, and also the excision of the embryonic axis followed by cryopreservation (Bonjovani 2011;Ribeiro et al 2016a). Silva-Júnior & Pereira (2009) and Lorenzi (2009) also describe R. grandis germination with rates around 50% when sown soon after harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Bandeira et al (2018) worked with an important weed, Senna obtusifolia, and found that the germination percentage of the species is maximized at the temperature of 25 ºC. For the species Senna multijuga, the temperatures of 30 ºC (constant) and 20-30 ºC (alternating) resulted in the highest germination percentage (Ribeiro et al, 2016). Wang et al (2017) reported that the best temperatures for germination in the species Digitaria sanguinalis were between 25 and 35 ºC.…”
Section: Second Experimentsmentioning
confidence: 99%
“…Londrina, v. 43, n. 6, p. 2785-2802, nov./dez. 2022 alternating temperatures, which correspond to the environmental conditions found in the natural environment (Ribeiro et al, 2016). Fontes et al (2019) evaluated the influence of light and water stress on the germination behavior and vigor of Amaranthus deflexus and found that water stress negatively affects seed performance, reducing germination and vigor, whereas the absence of light completely compromised germination, regardless of the stress level applied.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of seedlings to tolerate water loss to the environment may characterize a high capacity of survival, even in environments with higher water restrictions [11]. In semi-arid environments, such as Caatinga, a seasonally dry tropical forest, rain events at short intervals of time promote deficit conditions in all phases of plant development.…”
Section: Introductionmentioning
confidence: 99%